Strategi Pembangunan Pariwisata Melalui Sinergitas Dinas Pariwisata dengan Desa Adat ( Studi Kasus pada Pengelolaan Obyek Wisata Pantai Labuan Sait dalam Meningkatkan Retribusi Daerah Di Kabupaten Badung) - Suci Widyawati, Ni Wayan (Jurnal Nawala Politika, 2025)
A gradual Tourism development is very important to improve the quality of tourism each year to compete with other tourist attraction. The synergy between the Central Government with local government plays an important role to the development of tourism. The background to this research is the development of tourism which is still insufficient in Labuan Sait both in terms of means and infrastructure, promotion, as well as structuring tourism. This study measures how does tourism development strategy through the synergy with the customary village tourism office on the management of Beach Tourism Labuan Sait in increasing the levy County in Badung Regency with the theory of development that uses the concept of planning development by Sjahrizal in the regional development planning in the era of autonomy. The indicator consists of planning, implementation, monitoring and evaluation. In addition also use the concept of synergy from Najiyati and Rahmat which consists of indicators communication and coordination as well as indicators of the SWOT by Freddy Rangkuti. Method used in this study is a qualitative method with descriptive approach with data collection techniques in the form of in-depth interviews to several informants associated with this research. The results of the research showed that the development strategy of tourism through the synergy with the customary village Tourism Office on the management of Beach Tourism Labuan Sait in improving regional levies in Badung Regency are still insufficient. That is because the is still lacking from the indicator monitoring and implementation and evaluation of the impact against the decline of levy of admission attractions Labuan Sait in the 2017.     Keywords: Development, Tourism, Synergy, and Strategy